Safety of the COVID-19 vaccination in children with juvenile idiopathic arthritis—A observational study from two pediatric rheumatology centres in Poland - Opoka-Winiarska, Violetta; Lipinska, Joanna; Michalak, Arkadiusz; Burzyński, Jacek; Kądziołka, Olga; Smolewska, Elżbieta (Frontiers in Pediatrics, 2023)
Introduction The safety of COVID-19 vaccines in children with juvenile idiopathic arthritis (JIA) is the concern of patients and their parents and doctors in the current pandemic reality. The main objective of the study was to evaluate the safety of COVID-19 vaccine in patients with JIA. Method A cohort study based on short clinical follow-up of 43 children with JIA was conducted in the years 2021-2022 in two centres of paediatric rheumatology in Poland. All patients received mRNA COVID-19 vaccine. The patients’ data were collected using appropriate validated questionnaire. Disease activity was evaluated using Juvenile Arthritis Disease Activity Score 27-joint count (JADAS-27). Results Ten (22.7%) children had COVID-19 infection before getting COVID-19 vaccine. After first dose of COVID-19 vaccine 25/43 (58.1%) patients presented typical adverse events: arm pain or oedema at the application side or weakness. Also, twenty five (58.1%) children had side effects after second dose of this vaccine, however the spectrum of the symptoms was wider (additionally: headache, fever, lymphadenopathy, arrhythmia). Thirteen out of 43 (30.2%) patients had active disease before and 8/43 (18.6%) after COVID-19 vaccination, while the degree of JADAS-27 activity was higher in the study group before COVID-19 vaccination (p = 0.047). Conclusions Our study found out that children and adolescents with JIA with remission without treatment or on the long-term treatment – cDMARDs or even bDMARDs, can be safely vaccinated for COVID-19. Moreover, the study found that COVID-19 vaccination does not interfere with the JIA treatment and does not exacerbate symptoms of the disease and that vaccination protected against developing COVID-19 in children with JIA even on treatment.